2011
DOI: 10.1007/s00464-011-1745-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel technique of overlaying a poly-l-lactic acid nanosheet for adhesion prophylaxis and fixation of intraperitoneal onlay polypropylene mesh in a rabbit model

Abstract: Overlaying of a PLLA nanosheet was effective for adhesion prophylaxis of intraperitoneal mesh. It also may have a possible beneficial effect on fixation of mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…Consistent with previous reports (8), when the repaired tissue was placed back inside the abdominal cavity the film did not stick to any opposing tissues and remained adherent strictly to the treatment site.…”
Section: In Vivo Study Observations and Histologysupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previous reports (8), when the repaired tissue was placed back inside the abdominal cavity the film did not stick to any opposing tissues and remained adherent strictly to the treatment site.…”
Section: In Vivo Study Observations and Histologysupporting
confidence: 89%
“…This same group also demonstrated the efficacy of PLLA sheets as a method for fixing a polypropylene mesh in the peritoneal cavity without inducing visceral adhesions during open surgery (8).…”
Section: Introductionmentioning
confidence: 92%
“…35,45,46 The composition of these coatings varies from synthetic materials including polymers and metal films, 39,47,48 to biologic materials. Biologic mesh coatings include purified collagen, 40 gelatin, 35 hyaluronic acid, 42–44 chitosan, 38 cellulose, 16,39,43 and fatty acids. 39,43 Several of these biologic coating materials are isolated from ECM but in highly purified forms rather than the complex mixture found in the native ECM microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…4b). 57 The results evidenced that PLA FsNMs are feasible to induce adhesion prophylaxis in the IPOM, having a beneficial effect as an atraumatic fixation tool. In addition, it was found that nanosheets do not cause inflammatory reaction, which was attributed to the excellent biocompatibility of PLA.…”
Section: Polyester Free-standing Nanomembranesmentioning
confidence: 96%